Learning study, economics and cognitive bias: what is the object of learning?. Issue 3 (13th July 2015) - Ulla Runesson, Professor; Wood, Keith; Lu, Crystal; Andrew, Vincent
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to report how teachers have engaged in a Learning Study to develop, from the experience of their students, an object of learning which has important implications for pedagogy. Design/methodology/approach – This paper uses a Learning Study of the economic concept of price over three cycles with varying groups of high school students which explored the effect of context and cognitive bias on the learners' understanding of the object. Findings – The object of learning has the following critical aspects: the attributes of the commodity, the exchange mechanism (e.g. the market structure) and consumer rationality. This finding enriches the critical aspects – supply and demand – of the object of learning price found in the current Learning Study literature and current high school textbooks. Originality/value – Making explicit the variation between mainstream and behavioural models of economic phenomena helps learners to see what is critical – to see the potential and the limitations of those models for understanding the world and acting within it. Without sight of an alternative model it is impossible for the learner to distinguish between the mainstream model of supply and demand and what it purports to describe. Without behavioural dimensions, economics may not appear relevant to consumer decision-making.